Kepemimpinan Kepala Madrasah Era Disrupsi: Revitalisasi Nilai Religius-Interdisipliner Siswa - Sabililhaq, Irhas; Dina, Sarah; Khatami, Mohammad; Suryanudin, Chusnunnisa’ (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
The era of disruption has brought various impacts, including the world of education which is experiencing a multidimensional crisis and a moral crisis. Two important characteristics, namely religious attitude and discipline, slowly began to disappear in the personality of the nation's generation. Responding to this, the leadership of a school principal must have the courage to be faced with renewal and innovation, so that strengthening student character can still run optimally in the current era. This research uses a descriptive type with a qualitative approach which involves the Head of Madrasah 'Aliyah Negeri 1 Sleman as the research subject. Data were collected by researchers using observation, interview, and documentation techniques. The purpose of this study was to determine the leadership style of the madrasa head in his efforts to revitalize students' religious-interdisciplinary values. The findings of this study include that the leadership style of the head of Madrasah 'Aliyah Negeri 1 Sleman applies democratic leadership, using a familial approach. The principle applied in leadership is zero-accident, in line with the leadership model in the era of disruption, namely responsible leadership where all elements are involved in advancing educational institutions. Some of the efforts and strategies of the head of Madrasah 'Aliyah Negeri 1 Sleman in revitalizing students' religious-interdisciplinary values ​​are the discipline of obligatory and sunnah prayers, muezzin scheduling, reading asma'ul husna, preacher training, class recitation, religious competitions, tabligh akbar, PPBN (Preliminary State Defense Education), reward and punishment-based Control Books, state commemoration ceremonies/calls, madrasa camps, LDK (Basic Leadership Training), and Activation of Organizational Activities. Furthermore, the inhibiting factors for the revitalization of students' religious-interdisciplinary values ​​by the head of the madrasa are environmental factors, peers, self-awareness, and lack of parental attention.